Edukasi Pemanfaatan Terapi Komplementer Jahe dalam Asuhan Kebidanan untuk Mengurangi Mual Muntah Ibu Hamil - Nur Maziyah Hurin'in; Tri Yunita Fitria Damayanti (Jurnal Pengabdian Masyarakat - PIMAS, 2023)
Nausea and vomiting of pregnancy and hyperemesis gravidarum are related to biological, physiological, psychological and sociocultural factors but the exact etiology of nausea and vomiting in pregnancy is not clearly known. Genetic factors are stated to increase the risk of nausea and vomiting. Endocrine factors, especially increased HCG, play a role as a trigger for nausea and vomiting in pregnancy until hyperemesis gravidarum occurs. This community service activity was carried out using audio-visual media in the form of a video on making a white ginger drink and providing material on nausea and vomiting in pregnancy and how to handle it at home. Respondents to this community service activity were all pregnant women in the Polinlur Permata Bunda Tuban work area. Respondents were given leaflets and given a copy of the video for making ginger drink. Follow-up community service activities to evaluate the behavior of pregnant women after receiving this education, they can use this complementary therapy to reduce nausea, vomiting, especially in the morning in pregnant women. There is an increase in knowledge after being given education on the use of ginger for nausea and vomiting in pregnant women. This community service is one of the stimulations of community empowerment to improve health, especially for pregnant women by using ginger as a complementary therapy because there are few side effects and can be obtained around and easy to practice